Early Refractive and Clinical Outcomes of High-Myopic Photorefractive Keratectomy as an Alternative to LASIK Surgery in Eyes with High Preoperative Percentage of Tissue Altered. (28th January 2019) - Sorkin, Nir; Rosenblatt, Amir; Smadja, David; Cohen, Eyal; Santhiago, Marcony R.; Varssano, David; Yatziv, Yossi
Abstract : Objective . To analyze the safety and efficacy of high-myopic PRK as an alternative to LASIK surgery in patients with a high preoperative percentage tissue altered (PTA). Design . Retrospective interventional case series. Participants. Charts of 256 consecutive eyes that underwent PRK with application of mitomycin-C 0.02% for high myopia were retrospectively reviewed. Methods . Refractive (refraction and refractive accuracy) and visual outcomes (uncorrected and corrected visual acuities), as well as occurrence of haze in the eyes with preoperative PTA expected to be higher than 40% with a 110-micron flap if undergoing LASIK surgery, were analyzed. Results . Mean follow-up was 7.3 ± 4.8 months. A total of 187 of 256 eyes (73.0%) were included in the analysis because they were expected to have a PTA greater than 40%, should they have undergone LASIK surgery. The actual mean PTA of those eyes following PRK was 31.8 ± 2.2%, and none had a PTA ≥ 40%. UDVA of 20/16, 20/20, and 20/25 or better was achieved in 1.2% (2 eyes), 65.5% (112 eyes), and 85.4% (146 eyes), respectively. The percentage of eyes with postoperative SE within ±0.5 D and ±1.0 D of planned SE was 71% and 93%, respectively. None of the eyes lost 2 or more lines of CDVA. The rate of stromal haze, managed successfully with topical steroids only, was 4.8%. Conclusion . High-myopic PRK with application of mitomycin-C in the eyes at risk of developing ectasia because of high preoperative PTA was demonstrated to be a safe and effective alternative to the LASIK procedure.